Proceedings of the 3rd International Conference on Embedded Networked Sensor Systems 2005
DOI: 10.1145/1098918.1098922
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for establishing pairwise keys for securing wireless sensor networks

Abstract: Wireless sensor networks based on highly resource-constrained devices require symmetric cryptography in order to make them secure. Integral to this is the exchange of unique symmetric keys between two devices. In this paper, we propose a novel decentralized key exchange protocol that guarantees the confidentiality of a key exchange even if an attacker has compromised some of the devices in the network. A central objective of the protocol design was to minimize resource consumption on the individual devices. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Pairwise key schemes [16,24] attempt to mitigate the threat of compromised nodes by establishing shared keys that are held by only a small subset of network nodes. Unfortunately, this strategy is not sufficiently effective for network reprogramming protocols.…”
Section: Current Approachesmentioning
confidence: 99%
“…Pairwise key schemes [16,24] attempt to mitigate the threat of compromised nodes by establishing shared keys that are held by only a small subset of network nodes. Unfortunately, this strategy is not sufficiently effective for network reprogramming protocols.…”
Section: Current Approachesmentioning
confidence: 99%
“…The encryption scheme will be used to encrypt the entire SIP Message packet except for the "TO" field in the header, the key distribution scheme [9] helps transmit the symmetric key securely which will be used as a session key for later on message exchange. The new proposed architecture helps us to achieve an end to end encryption thus overcoming the draw backs of today's hop-by-hop way of encryption in VoIP.…”
Section: Proposed Architecturementioning
confidence: 99%
“…Every block is the routed through the internet cloud and it is suggested that all the 8 blocks of key be routed through different routes [9]. This decreases the probability of a key being compromised.…”
Section: Figure 4: Key Exchangementioning
confidence: 99%
“…In the basic protocol [3], random keys are pre-distributed. In the KP protocol variant in [4], unique pairwise keys are distributed into pairs of sensors [3], q − composite [4], direct/cooperative [8], random keys probabilistic [9], deployment knowledge [11], P IKE [12], RKEP [13], conf iguration/intersection [15] nature of distributed keys unique pairwise keys random pairwise key [4], closest pairwise key [7], GKE [16] multi − space [5], random subset [6], grid based [6], random key structures location based [7], location aware [10], hexagonal grid [14], multivariate [17] [18] key setup basic protocol [3], q − composite [4], multivariate [17] [18], random multi − space [5], random subset [6], direct/cooperative [8], probabilistic [9], RKEP [13], key distribution method random pairwise key [4], closest pairwise key [7] optimization design conf iguration/intersection [15] quorum based grid based [6], P IKE [12] grid based location based [7], location aware [10], deployment knowledge [11], hexagonal grid [14], GKE [16] closest pairwise key/location based [7], location aware [10], aware deployment knowledge [11], hexagonal grid …”
Section: ) Enhancement In Key Setup Stagementioning
confidence: 99%
“…grid based [6], closest pairwise key/location based [7], maximum number of hops cooperative [8], P IKE [12], RKEP [13], intersection [15] on one key path 3 location aware [10], GKE [16] basic protocol [3], q − composite [4], multi − space [5], ∞ random subset [6], probabilistic [9], deployment knowledge [11], multivariate [17] [18] chosen randomly. Resilience is enhanced at the cost of poor connectivity in large scale networks under memory constraints.…”
Section: ) Enhancement In Key Setup Stagementioning
confidence: 99%